2021
DOI: 10.3390/catal11040506
|View full text |Cite
|
Sign up to set email alerts
|

Removal of VOCs by Ozone: n-Alkane Oxidation under Mild Conditions

Abstract: Volatile organic compounds (VOCs) have a negative effect on both humans and the environment; therefore, it is crucial to minimize their emission. The conventional solution is the catalytic oxidation of VOCs by air; however, in some cases this method requires relatively high temperatures. Thus, the oxidation of short-chain alkanes, which demonstrate the lowest reactivity among VOCs, starts at 250–350 °C. This research deals with the ozone catalytic oxidation (OZCO) of alkanes at temperatures as low as 25–200 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In contrast, the ozonation of alkanes has been reported at lower and even sub-ambient temperatures compared to those for oxidation with dioxygen. Ozone readily oxidizes propane, n -butane, and isobutane in the gas phase at 50 °C and ambient pressure. Isobutane is oxidized to tert -butyl alcohol at ∼50% selectivity with a CO 2 selectivity of ∼16% .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the ozonation of alkanes has been reported at lower and even sub-ambient temperatures compared to those for oxidation with dioxygen. Ozone readily oxidizes propane, n -butane, and isobutane in the gas phase at 50 °C and ambient pressure. Isobutane is oxidized to tert -butyl alcohol at ∼50% selectivity with a CO 2 selectivity of ∼16% .…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed this improved performance to the enhanced textural and redox properties of the modified red mud due to the better dispersion and higher enrichment of Fe oxides at their surface. Mytareva et al [8] investigated the ozone catalytic oxidation of alkanes by using an alumina-supported manganese oxide catalyst. They demonstrated that the presence of a small amount of ozone in air allowed to significantly decrease the temperature range of n-alkane oxidation, since 80-100% conversion is achievable in the temperature range 70-200 • C over Mn (10 wt.%)/Al 2 O 3 catalyst.…”
mentioning
confidence: 99%